Uji Efektivitas Pestisida Nabati Kombinasi Ekstrak Chromolaena odorata L. dan Annona muricata L. terhadap Mortalitas Hama Ulat Daun (Plutella xylostella) - Binti Choirul Latifa; Nanang Tri Haryadi (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2024)
P. xylostella is one of the main pests of cabbage plants. A combination of kirinyuh and soursop leaves is an effort to increase the effectiveness in controlling P. xylostella. The purpose of this study was to determine the effect of a combination of kirinyuh and soursop leaf extract on the mortality, toxicity, and feeding activity of P. xylostella. The application technique used was the feed dipping method on a laboratory scale. The experimental design used CRD (Completely Randomized Design), the experiment consisted of 7 treatments namely control, a single extract of kirinyuh leaves concentration of 40%, a single extract of soursop leaves with concentration of 40%, a combination extract kirinyuh and soursop leaves concentrations 10%, 20%, 30%, and 40%. Data were analyzed by analysis of variance and DMRT 5% for follow-up test. The results showed that the combination of extracts had an effect on the mortality, toxicity, and feeding activity of P. xylostella. The highest mortality was 51,72% at a combined concentration of 40%. The LC50 value was 36,61% and the LT50 value was 5,26 days at a combined concentration of 40%. The highest inhibition of eating activity with a value of 90% at a combined concentration of 40%.